Exosomes Transfer Among Different Species Cells and Mediating miRNAs Delivery. Issue 12 (25th May 2017) - Zhou, Yueyuan; Tian, Tian; Zhu, Yanliang; Jaffar Ali, Doulathunnisa; Hu, Feihu; Qi, Yuhua; Sun, Bo; Xiao, Zhongdang
ABSTRACT: Exosomes, the natural vehicles of intercellular communication, transfer proteins, mRNAs, and microRNAs (miRNAs) and mediate many physiological and pathological processes. It is not clear that whether exosomal miRNAs could regulate gene expression across species, though some studies suggest interactions of exosomal miRNAs between cells. In this report, we have isolated exosomes from rat PC12 cells and assessed their internalization by human cancer Hela cells. The internalized exosomes were located in Hela lysosomes. Human PTEN expression was significantly deregulated due to miR‐21 delivered by rat cell exosomes. Our results prove that exosomes could incorporate between cells of different species and could regulate the protein expressions in the recipient cells by delivering the enclosed miRNAs. Thus our study foreshadows a futuristic treatment approach of utilizing miRNA enclosed exosome vehicles sans species concerns in combating various diseases/ regulating abnormal proteins. J. Cell. Biochem. 118: 4267–4274, 2017. © 2017 Wiley Periodicals, Inc. Abstract : In this work, exosomes isolated from rat PC12 cell were internalized by human cancer Hela cells and located in Hela lysosomes. Human PTEN expression in Hela was significantly deregulated due to miR‐21 delivered by PC12‐derived exosomes.